Comparison of the Performances of (18)F-FP-CIT Brain PET/MR and Simultaneous PET/CT: a Preliminary Study - Kwon, SangDon (Nucl Med Mol Imaging, 2016)
PURPOSE: (18)F-FP-CIT [(18)F-fluorinated N-3-fluoropropyl-2-beta-carboxymethoxy-3-beta-(4-iodophenyl) nortropane] has been well established and used for the differential diagnosis of atypical parkinsonian disorders. Recently, combined positron emission tomography (PET)/magnetic resonance (MR) was proposed as a viable alternative to PET/computed tomography (CT). The aim of this study was to compare the performances of conventional (18)F-FP-CIT brain PET/CT and simultaneous PET/MR by visual inspection and quantitative analysis. METHODS: Fifteen consecutive patients clinically suspected of having Parkinson’s disease were recruited for the study.(18)F-FP-CIT PET was performed during PET/CT and PET/MR. PET/CT image acquisition was started 90 min after intravenous injection of (18)F-FP-CIT and then PET/MR images were acquired. Dopamine transporter (DAT) density in bilateral striatal subregions was assessed visually. Quantitative analyses were performed on bilateral striatal volumes of interest (VOIs) using average standardized uptake values (SUVmeans). Intraclass correlation coefficients (ICCs) and their 95 % confidence intervals (CIs) were assessed to compare PET/CT and PET/MR data. Bland–Altman plots were drawn to perform method-comparisons. RESULTS: All subjects showed a preferential decrease in DAT binding in the posterior putamen (PP), with relative sparing of the ventral putamen (VP). Bilateral striatal subregional binding ratio (BR) determined PET/CT and PET/MR demonstrated close interequipment correspondence (BR(right caudate) - ICC, 0.944; 95 % CI, 0.835–0.981, BR(left caudate) - ICC, 0.917; 95 % CI, 0.753–0.972, BR(right putamen) - ICC, 0.976; 95 % CI, 0.929–0.992 and BR(left putamen) - ICC, 0.970; 95 % CI, 0.911–0.990, respectively), and Bland–Altman plots showed interequipment agreement between the two modalities. CONCLUSIONS: It is known that MR provides more information about anatomical changes associated with brain diseases and to enable the anatomical allocations of subregions than CT, though this was not observed in the present study. Although the subregional BR of simultaneous PET/MR was comparable to that of PET/CT in Parkinson’s disease, our isocontouring method could make bias. A future automated method using standard template study or manual segmentation of putamen/caudate based on MR or CT is needed.